Integrated National Climate and Energy Policies and Measures (PaM), 2024 ... - European Environment Agency; Perez, Rodrigo (European Environment Agency, 2024)
This database contains a number of integrated national climate and energy policies and measures (PaM) implemented or planned by European countries to reduce greenhouse gas emissions, and achieve climate and energy targets. This data is reported in accordance with the Governance Regulation (2018/1999) Articles 17 and 18. Most of these PaMs have been additionally reported to the European Commission via National Energy and Climate Plans (NECPs) or to the United Framework Convention on Climate Change (UNFCCC) Biennial Transparency Reports (BTR). Only Estonia, Ireland, Sweden updated their data in 2024. This dataset consists of the updated data for these countries and then the latest reported data from the other EU27 countries in 2023. This dataset only includes core reporting elements from Implementing Regulation 2020/1208 Annex XXIV and Implementing Regulation 2022/2299 Annex IX and not all additional energy related reported information as normally required under the National Energy and Climate Progress ...